Assessing the quality of medical care and developing the ratings of health services: experience of using Medicare program in the USA - N. S. Grigorieva (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
To provide patient's security is the main goal in some spheres of health care, that is why methods of statistical monitoring were developed to detect abnormalities in the course of medical work quickly and confidentially. This includes, for example, excessive intervention even without further damage to a patient's safety. Therefore, it is very important to determine whether the risk to a patient's life exists or how abnormal the situation is. At the present moment health care in Russia has already passed the initial stage of formation of ratings to assess the quality of medical care services. Almost all regions of the Russian Federation have their own ratings. The question is how objectively they reflect the quality of medical services. The article presents main features to assess the quality of health care to rate medical organizations on the example of state program Medicare (USA) in order to compare them with the ones used in Russian ratings.